Zinc borate modified multifunctional ceramic diaphragms for lithium-ion battery. Issue 17 (1st September 2022) - Cheng, Hongyu; Hou, Jiyue; Wang, Yanjie; Zhu, Ziyi; Zhang, Yiyong; Li, Xue; Zhang, Yingjie
Abstract: Polyethylene(PE) diaphragm has become broadly used in lithium-ion battery systems because of its high strength, exceptional plasticity, and resistance to organic solvents. Nevertheless, the lack of polar groups on the surface of the PE diaphragms has a little significant effect on the ionic polarity of the electrolyte. Consequently, the electrolyte has poor wettability, the lithium-ion migration number tLi + (0.21) and the ion conductivity σ (0.63 mS/cm) still need to be further improved, which restricts its application to a certain extent. In this work, the high-purity zinc borate modified PE diaphragms with Lewis acid sites were prepared via a simple solid-state method. The multifunctional diaphragms modified by zinc borate have the following advantages: (1) The Zn–O bond and -BO3 group in the structure have a polar bond and Lewis acid action, respectively, which can promote the desolvation of lithium ions and the dissociation of anions and cations, thereby increasing the concentration of free ions. In addition, zinc borate and anions have a specific binding effect, which can inhibit the migration of anions, consequently increasing tLi + (0.41) and σ (1.14 mS/cm); (2) Zinc borate was a commonly used flame retardant, which was conducive to improving the thermal stability of the PE diaphragms; (3) The surface of the modified diaphragms is rougher, which can increase the specific surface area of the diaphragm, hence enhancing its liquid absorption capacity. The electrochemical performance test results show that the modification of zinc borate can effectively improve the comprehensive performance of the PE diaphragm and the overall cycle stability and rate performance of the lithium iron phosphate battery.